EVALUATION AND IMPROVEMENT OF DRAINAGE PERFORMANCE IN GEDONGTATAAN, LAMPUNG USING DUFLOW MODELING STUDIO - Anna Mariana Situngkir (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2016)
Gedongtataan always experiences flooding annually with maximum inundation depth 0.5 m. Flood leads to road congestion. This study had objective to identify of the cause of flood, to assess the performance of drainage, and to propose the improvement options to cope the flood. The cause of flood was insufficient drainage capacity, less dimension, solid waste and grass weed in the drainage canals, lack of drainage along the road, and high rainfall. Duflow was one dimensional model used to assess the performance of drainage in existing condition, extreme condition, and some improvement options to cope the flooding which were Scenario 1 cleaning canals from solid waste and grass weed, Scenario 2 dyke construction and canal widening, and Scenario 3 resizing canals, a combination of dredging and widening canals. The best improvement option was Scenario 3 resizing canals since it is long term solution and not costly to prevent the flood.